Single photon ionization of hydrogen bonded clusters with a soft x-ray laser: (HCOOH)x and (HCOOH)y(H2O)z - Heinbuch, S., author; Rocca, Jorge J., author; Dong, F., author; Bernstein, E. R., author; American Institute of Physics, publisher (Colorado State University. Libraries, 2007)
Pure, neutral formic acid (HCOOH)n+1 clusters and mixed (HCOOH)/(H2O) clusters are investigated employing time of flight mass spectroscopy and single photon ionization at 26.5 eV using a very compact, capillary discharge, soft x-ray laser. During the ionization process, neutral clusters suffer little fragmentation because almost all excess energy above the vertical ionization energy is taken away by the photoelectron, leaving only a small part of the photon energy deposited into the (HCOOH)+n+1 cluster. The vertical ionization energy minus the adiabatic ionization energy is enough excess energy in the clusters to surmount the proton transfer energy barrier and induce the reaction (HCOOH)+n+1 →(HCOOH)nH++HCOO making the protonated (HCOOH)nH+ series dominant in all data obtained. The distribution of pure (HCOOH)nH+ clusters is dependent on experimental conditions. Under certain conditions, a magic number is found at n=5. Metastable dissociation rate constants of (HCOOH)nH+ are measured in the range (0.1-0.8) × 104 s−1 for cluster sizes 4<n<9. The rate constants display an odd/even alternating behavior between monomer and dimer loss that can be attributed to the structure of the cluster. When small amounts of water are added to the formic acid, the predominant signals in the mass spectrum are still (HCOOH)nH+ cluster ions. Also observed are the protonated mixed cluster series (HCOOH)n(H2O)mH+ for n=1-8 and m=0-4. A magic number in the cluster series n=5, m=1 is observed. The mechanisms and dynamics of formation of these neutral and ionic clusters are discussed.